THE RELATIONSHIP BETWEEN HEALTH LOCUS OF CONTROL AND DIET COMPLIANCE IN TYPE 2 DIABETES MELLITUS PATIENTS IN THE WORK AREA OF KABILA COMMUNITY HEALTH CENTER BONE BOLANGO REGENCY - Citra Magfira Nihe (PT. Jurnal Center Indonesia Publisher, 2025)
Diabetes mellitus is a disease characterized by increased glucose levels that over time cause serious damage to the heart, blood vessels, eyes and kidneys ( World Health Organization) in 2024. Compliance is the degree to which a person carries out health-related behavior, either taking medication, following diet therapy and changing lifestyle according to recommendations given by health workers. Diet or nutritional therapy is used to regulate the patient's food intake so that it remains fulfilled and does not result in an increase in blood sugar so that it is necessary to regulate the schedule, type and amount of food as nutrition. This study aims to determine whether there is a relationship between health locus of control and compliance with diet in patients with diabetes mellitus in the Kabila Health Center work area. The design in this study is quantitative correlational. The sampling technique in this study used the non-probability sampling method with a total sample of 52 diabetes mellitus participants at the Kabila Health Center. The instrument used in the study used a questionnaire instrument with open questions about the variable health locus of control and compliance with the diet of patients with diabetes mellitus. Based on the results of the study, there is a relationship between health locus of control and compliance with diet in diabetes mellitus patients in the Kabila Health Center work area, with a significance value or p-value showing 0.000 (p <0.05). This is based on the alternative Fisher exact test because there are 3 cells with an expect count value <5.